2014
DOI: 10.1007/s11270-014-2083-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spatial and Temporal Variation in Water Contamination Along Croatian Highways by Multivariate Exploratory Analysis

Abstract: In the research, in this paper, we investigate spatial and temporal variations in the composition of wastewater near Croatian highways in three climatic regions (continental, Mediterranean, highland) during three seasons (autumn, winter and spring). In our paper, the spatial division of the investigated areas that pertain to the three aforementioned climatic regions was obtained using the method of hierarchical clustering of monitored locations. One thousand five hundred thirty-three samples from 14 locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The results showed that there were two different water qualities in the catchment area. It implied that for rapid assessment of water quality, only one station in each cluster may serve as good in spatial assessment of the water quality as the whole network (Li et al 2014;Xu et al 2014;Dobsa et al 2014). The CA technique reduced the need for numerous sampling stations.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that there were two different water qualities in the catchment area. It implied that for rapid assessment of water quality, only one station in each cluster may serve as good in spatial assessment of the water quality as the whole network (Li et al 2014;Xu et al 2014;Dobsa et al 2014). The CA technique reduced the need for numerous sampling stations.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Zhang et al (2011) studied the spatial-temporal variations of water quality obtained from the watercourses in the Southwest New Territories and Kowloon, Hong Kong. Dobsa et al (2014) investigated spatial-temporal variations in the composition of water contamination near Croatian highways in three climatic regions during three seasons using multivariate statistical techniques. Vieira et al (2012) evaluated the spatial variations of Lis river basin surface water, Portugal.…”
mentioning
confidence: 99%
“…The presence of heavy metals may be a result of natural processes but could also be related to metal corrosion from vehicles and highway infrastructure. It is known that the main sources of some heavy metals such as cadmium, copper, lead, nickel and zinc are the traffic, domestic heating and long-range transport [11,39,40]. The dispersion of metals is influenced by meteorological conditions like wind, rainfall and traffic intensity.…”
Section: Heavy Metals In the Soilmentioning
confidence: 99%
“…Due to the high population density and intensive anthropogenic activities, urban soils have been severely disturbed and heavy metal pollution remains as a major issue. The influence of traffic on pollution in top soils near highways is well documented [11]. Heavy metals may originate and reach urban soils in a variety of ways such as vehicle wear (including tyres, brakes and engine) as well as to leaking oil and corrosion, chemical industry, coal combustion, municipal solid waste, the sedimentation of dust and suspended substances in the atmosphere and other activities [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation